Kajian Hukum Terhadap Perlindungan Whistleblower Dalam Perkara Tindak Pidana Korupsi - Asliani Asliani; Ismail Koto (Iuris Studia: Jurnal Kajian Hukum, 2022)
Whistleblower is someone who reports an act against the law, especially corruption in the organization or agency where he works. In the investigation process, whistleblower information is needed as a key witness to uncover the truth of the facts committed by the perpetrators who require legal protection from the government and law enforcement officers who are submitted to the Witness and Victim Protection Agency in order to maintain the safety of themselves and their families as well as assets in accordance with applicable legal regulations. The purpose of this study is to determine the protection of whistleblowers as key witnesses who provide information about criminal acts that have occurred. In this research, normative juridical research is used to process data from primary legal materials, secondary legal materials and tertiary legal materials. Whistleblowers get protection from the authorities to reveal a legal truth about criminal acts of corruption in accordance with laws and regulations with certain limits in a business. especially the police in coordination with the Witness and Victim Protection Agency (LPSK) which has the authority to provide legal protection to the judicial process in accordance with statutory regulations